2020
DOI: 10.1038/s41598-019-56897-8
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Pre-conditioning Ameliorates Diabetic Myocardial Ischemia/Reperfusion Injury Via Differential Regulation of p38 and ERK

Abstract: Diabetes mellitus (DM) significantly increases myocardial ischemia/reperfusion (MI/R) injury. During DM, cardioprotection induced by conventional pre-conditioning (PreCon) is decreased due to impaired AMP-activated protein kinase (AMPK) signaling. The current study investigated whether PreCon with inhaled anesthetic sevoflurane (SF-PreCon) remains cardioprotective during DM, and identified the involved mechanisms. Normal diet (ND) and high-fat diet (HFD)-induced DM mice were randomized into control and SF-PreC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…Excessive apoptosis is associated with myocardial ischemia, I/R injury as well as postischemia cardiac remodeling [18], while infarct size is an independent indicator effective in predicting mortality after infarction [19]. In the current work, we observed that Sev worked as a cardio-protector against injury induced by myocardial I/R by reducing LVEF, LVFS, myocardial infarct size and apoptosis rate, indicating the bene cial role of Sev on I/R injury [20,21]. Moreover, Sev was found to diminish NEAT1, which was enhanced in mice with myocardial I/R, by microarray analysis.…”
Section: Discussionsupporting
confidence: 53%
“…Excessive apoptosis is associated with myocardial ischemia, I/R injury as well as postischemia cardiac remodeling [18], while infarct size is an independent indicator effective in predicting mortality after infarction [19]. In the current work, we observed that Sev worked as a cardio-protector against injury induced by myocardial I/R by reducing LVEF, LVFS, myocardial infarct size and apoptosis rate, indicating the bene cial role of Sev on I/R injury [20,21]. Moreover, Sev was found to diminish NEAT1, which was enhanced in mice with myocardial I/R, by microarray analysis.…”
Section: Discussionsupporting
confidence: 53%
“…[ 27 ] Sevoflurane preconditioning mitigates the ischemia-reperfusion injury and improves the cardiac function. [ 28 29 30 ] Erturk et al . observed that sevoflurane provides better protection from ischemic reperfusion injury in thoracic surgical patients after one lung ventilation compared to propofol by lower rise in malondialdehyde and ischemia modified albumin levels during the perioperative period.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, rats with ALI downregulates α-, β-and γ-ENaC expressions and ADSCs could reverse the ALI-induced reduction of three ENaC subunits levels. Sevoflurane has been shown to reduce mortality via non-anesthetic properties in clinical patients 48 , and has been widely accepted to reduce the levels of inflammatory mediators (IL-1β, TNFα, and IL-6) 49 . Although ADSC treatment was more effective than sevoflurane in the current research, previous studies showed that sevoflurane had cytoprotective effects in ARDS and ALI 50 .…”
Section: Discussionmentioning
confidence: 99%